Serum multi-trace elements and post-stroke cognitive impairment: a prospective observational cohort study - Ruolin Zhou; Weijie Zhai; Lingjie Meng; Chunxiao Wei; Li Sun (Translational Psychiatry)
Abstract Post-stroke cognitive impairment (PSCI) significantly affects stroke survivors. Identifying modifiable risk factors for PSCI is essential. Serum multi-trace elements are crucial for neurological function but vary in concentration among older adults. It remains unclear whether increasing multi-trace elements can reduce the incidence of PSCI. We investigated the associations between baseline serum multi-trace elements and PSCI. The Montreal Cognitive Assessment defined PSCI. We used logistic regression analyses to evaluate the association between serum multi-trace elements and PSCI. Subsequently, we assessed the associations between serum multi-trace elements and three different cognitive domains using the Kruskal–Wallis test. We further evaluated improvements in the predictive ability of serum multi-trace elements. Finally, 626 patients (mean age: 62.85 ± 7.54 years) were followed up for a median of 1.2 years. Lower concentrations of serum iron (odds ratio [OR] = 2.498, 95% confidence interval [CI]: 1.505–4.145) and zinc (OR = 2.015, 95% CI: 1.233–3.293) were associated with a higher PSCI risk. Higher concentrations of serum iron (OR = 0.368, 95% CI: 0.227–0.595) and magnesium (OR = 0.273, 95% CI: 0.164–0.454), along with lower concentrations of serum copper (OR = 0.544, 95% CI: 0.34–0.872), were significantly correlated with a lower PSCI risk. Cognitive impairments varied across multi-trace elements. Serum iron affected wider cognition, while magnesium and copper levels were strongly associated with language and executive function. Adding serum multi-trace elements to the conventional model improved PSCI risk reclassification (area under curve: 0.676–0.718). Multi-trace elements may influence PSCI progression. This study was registered with the Chinese Clinical Trial Registry (URL: https://www.chictr.org.cn/ ; unique identifier: ChiCTR1900022675).